Studies on the Vertical Distribution of Ticks of Domestic Animals and Their Public Health Importance in Nilgiri Hills and Adjoining Areas of Tamil Nadu State (India) - Kumar, Kaushal; Balakrishnan, N.; Sharma, Abhay Kumar (International Journal of Zoology, 2014)
The Nilgiri hills and adjoining downhill areas provide favourable ecological conditions for the propagation of haematophagous arthropods owing to richness in vegetation and animal activities. A study has been undertaken during 2008–2010 on the distribution and abundance of ticks of domestic animals in seven different biotopes. A total of 3,008 domestic animals were examined in areas ranging from an altitude of 300 to 2200 meters above mean sea level (MSL) of which 1,335 (44.5%) animals were having tick infestation. A total of 6,012 adult and immature ticks belonging to 12 species (11 ixodid and one argasid) were collected. Eleven tick species were collected from Kallar area situated downhill eastern slopes of the Nilgiris followed by Burliar area (7 species) located at higher altitudes. From Masinagudi area near to dense forests and scrub jungles, five species were recorded. However, at higher elevations on the hills, Udhagamandalam area, only one species was recorded. Among various tick species recorded in the study, Boophilus microplus was distributed in almost all areas surveyed followed by Haemaphysalis spinigera and Rhipicephalus sanguineus. The factors governing their distribution and epidemiological significance in the transmission of various tick-borne diseases of public health importance are discussed.